The efficacy and safety of Chinese herbal medicine for reducing wound complications after anal fistula surgery: A protocol for systematic review and meta-analysis. Issue 48 (2nd December 2022) - Qi, Wenyue; Wang, Linyue; Xu, Jiancheng; Gao, Jihua
Abstract : Background: Anal fistula is one of the most common diseases in anorectal surgery. The wound healing after surgery can affect the prognosis of patients. We conducted a protocol for systematic review and meta-analysis to assess the efficacy and safety of Chinese herbal medicine for reducing wound complications after anal fistula surgery. Methods: We have prepared this protocol in accordance with the Preferred Reporting Item for Systematic Review and Meta-analysis (PRISMA-P) statement. We will search the following databases: the China National Knowledge Infrastructure, Wanfang Database, Chinese Science and Technology Periodical Database, Chinese Biomedical Literature Database, Pubmed, Embase, Web of Science, and the Cochrane library. Two authors will independently assess the risk of bias of the included studies based on the bias risk assessment tool recommended in the Cochrane "Risk of bias" assessment tool. All calculations are carried out with STATA13.0 software. Results: A synthesis of current evidence of Chinese herbal medicine for wound management after anal fistula surgery will be shown in this protocol. Conclusion: This study may provide more convincing evidence to help clinicians make decisions when dealing with anal fistula patients after surgery.